Integrated system for early fire detection and evacuation based on Arduino - Burgegulov, Akyltai; Mazakov, Talgat; Ziyatbekova, Gulzat; Jomartova, Sholpan; Mazakova, Aigerim (Statistics, Optimization & Information Computing, 2026)
In the present study, a system is developed to ensure an efficient and safe evacuation process in case of fire using modern threat detection and evacuation route optimization technologies. During the research, algorithms for analysing data from gas sensors, algorithms for optimizing evacuation routes based on graph theory, and software for integration with an Arduino microcontroller and real-time processing of the obtained data were developed and used. The research resulted in the development of an intelligent fire safety system based on Arduino microcontroller and MQ series gas sensors for early fire detection. The application of graph algorithms allowed determining the optimal evacuation paths, taking into account the building parameters and distribution of people. The system has shown high efficiency in calculating optimal evacuation routes, minimizing risks in emergency situations. It was revealed that the system’s integration with mobile applications and other smart city components has the potential to expand functionality and improve emergency coordination.